Complete mitochondrial genome of giant cricket Tarbinskiellus portentosus (Orthoptera: Gryllinae) and phylogenetic analysis - Cheng-Ye Wang; Pan-Li Yang; Zhao He; Long Sun; Min Zhao; Ying Feng (Mitochondrial DNA. Part B. Resources, 2022)
Tarbinskiellus portentosus (Lichtenstein, 1796) is an agricultural and forestry pest, but people in some places use it as a delicacy. The complete mitogenome of T. portentosus (GenBank accession number MZ427921) is 15, 498 bp in size, including 13 protein-coding genes, 22 transfer RNAs, two ribosomal RNAs genes, and a noncoding A + T-rich region. The A + T-rich region is located between 12S rRNA and tRNAIle. The base composition of the whole T. portentosus mitogenome is 40.62% for A, 9.87% for G, 32.20% for T, and 17.31% for C, with a high AT content of 72.82%. The phylogeny analysis indicated that T. portentosus had a close relationship with Cardiodactylus muiri. The present data could contribute to further detailed diversity and phylogeographic analysis for this edible cricket.